Report of the Meeting of the Ad Hoc Panel on the Measurement of Basic Quantities (The National Academies Press, 1961)

High-Magnetic-Field Research and Facilities: [Final Report] - National Research Council (The National Academies Press, 1979)

Plasma Science: From Fundamental Research to Technological Applications - National Research Council (The National Academies Press, 1995)
Plasma science is the study of ionized states of matter. This book discusses the field's potential contributions to society and recommends actions that would optimize those contributions. It includes an assessment of the field's scientific and technological status as well as a discussion of broad themes such as fundamental plasma experiments, theoretical and computational plasma research, and plasma science education.

High Magnetic Field Science and Its Application in the United States: Current Status and Future Directions - National Research Council
The Committee to Assess the Current Status and Future Direction of High Magnetic Field Science in the United States was convened by the National Research Council in response to a request by the National Science Foundation. This report answers three questions: (1) What is the current state of high-field magnet science, engineering, and technology in the United States, and are there any conspicuous needs to be addressed? (2) What are the current science drivers and which scientific opportunities and challenges can be anticipated over the next ten years? (3) What are the principal existing and planned high magnetic field facilities outside of the United States, what roles have U.S. high field magnet development efforts played in developing those facilities, and what potentials exist for further international collaboration in this area? A magnetic field is produced by an electrical current in a metal coil. This current exerts an expansive force on the coil, and a magnetic field is \

Innovations in Catalysis to Address Modern Challenges: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2023)
The National Academies of Sciences, Engineering, and Medicine Chemical Sciences Roundtable convened a workshop to discuss how the chemistry and chemical engineering communities can contribute practical solutions for improving chemical production through innovations in catalysis. Keynote presentations highlighted the implementation of sustainability in catalysis, including policy considerations and systems-level approaches to catalysis innovations. Throughout three presentation sessions, workshop participants discussed opportunities in various fields of catalysis, such as biocatalysis, electrocatalysis, and photocatalysis, as well as novel approaches to catalyst design and catalytic processes and reactions. The workshop also featured a session titled Vistas in Catalysis, in which 14 participants gave 3-minute presentations on topics ranging from photoelectrochemical water-splitting to machine learning in catalyst development. This publication summarizes the presentations and discussion of the workshop.

Data Science: Opportunities to Transform Chemical Sciences and Engineering: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2018)
New technologies and approaches are generating large, diverse data sets, and data science offers the tools that are needed to interrogate, analyze, and manage these data sets. Biology, material sciences, and other fields have embraced data science tools and used them to gain insights into, for example, gene2013environment interactions, molecular mechanisms of disease, and implications of material characteristics on performance. Chemical sciences and engineering have also used data science tools to, for example, monitor and control chemical processes, predict activity depending on chemical structures or properties, and inform business and research decisions. However, data science applications in the chemical sciences and engineering community have been relatively limited, and many opportunities for advancing the fields have gone unexplored. Accordingly, the National Academies of Sciences, Engineering, and Medicine held a workshop to explore opportunities to use data science to transform chemical sciences and engineering on February 27201328, 2018, in Washington, DC. Stakeholders from academia, government, and industry convened to discuss the challenges and opportunities to integrate data science into chemical sciences and engineering practice and data science training for the future chemical sciences and engineering workforce. This publication summarizes the presentations and discussions from the workshop.

Empowering Tomorrow's Chemist: Laboratory Automation and Accelerated Synthesis: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2022)
The National Academies of Sciences, Engineering, and Medicine's Chemical Sciences Roundtable convened a workshop on how best to automate the laboratory and train the next generation of chemists, chemical engineers, materials and formulation scientists, and others. This workshop explored the benefits of laboratory automation and opportunities to make this space more accessible for resource-limited institutions and identified ways to prepare the science, technology, engineering, and medicine workforce. Panel sessions gathered together researchers from industry, academia, and government to focus on the various aspects of automation in the chemical sciences, including the challenges and benefits of automation in industry, automation training and development of curricula in academia, and the future of automation in the industrial laboratories and universities. This publication highlights the presentation and discussion of the workshop.

Proposal Evaluation for Allocation of Supercomputing Time for the Study of Molecular Dynamics: Fourteenth Round - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2023)
The Committee on Proposal Evaluation for Allocation of Supercomputing Time for the Study of Molecular Dynamics, Fourteenth Round evaluated submissions received in response to a Request for Proposals for Biomolecular Simulation Time on Anton 2, a supercomputer designed and built by D. E. Shaw Research (DESRES). Over the past 13 years, DESRES has made an Anton or Anton 2 system housed at the Pittsburgh Supercomputing Center available to the non-commercial research community, based on the advice of previous committees of the National Academies of Sciences, Engineering, and Medicine. As in those prior rounds, the goal of the fourteenth RFP for simulation time on Anton 2 is to continue to facilitate breakthrough research in the study of biomolecular systems by providing a massively parallel system specially designed for molecular dynamics simulations. The program seeks to continue to support research that addresses important and high impact questions demonstrating a clear need for Antons special capabilities. This document describes the work and transmits the decisions of the Committee.

Reducing the Time from Basic Research to Innovation in the Chemical Sciences: A Workshop Report to the Chemical Sciences Roundtable - National Research Council (The National Academies Press, 2003)
Innovation, the process by which fundamental research becomes a commercial product, is increasingly important in the chemical sciences and is changing the nature of research and development efforts in the United States. The workshop was held in response to requests to speed the R&D process and to rapidly evolve the patterns of interaction among industry, academe, and national laboratories. The report contains the authors' written version of the workshop presentations along with audience reaction.

Assessing the Value of Research in the Chemical Sciences - National Research Council (The National Academies Press, 1998)
This book captures the messages from a workshop that brought together research managers from government, industry, and academia to review and discuss the mechanisms that have been proposed or used to assess the value of chemical research. The workshop focused on the assessment procedures that have been or will be established within the various organizations that carry out or fund research activities, with particular attention to the Government Performance and Results Act (GPRA). The book presents approaches and ideas from leaders in each area that were intended to identify new and useful ways of assessing the value and potential impact of research activities.

Nuclear Physics: Exploring the Heart of Matter - National Research Council (The National Academies Press, 2013)
The principal goals of the study were to articulate the scientific rationale and objectives of the field and then to take a long-term strategic view of U.S. nuclear science in the global context for setting future directions for the field. Nuclear Physics: Exploring the Heart of Matter provides a long-term assessment of an outlook for nuclear physics. The first phase of the report articulates the scientific rationale and objectives of the field, while the second phase provides a global context for the field and its long-term priorities and proposes a framework for progress through 2020 and beyond. In the second phase of the study, also developing a framework for progress through 2020 and beyond, the committee carefully considered the balance between universities and government facilities in terms of research and workforce development and the role of international collaborations in leveraging future investments. Nuclear physics today is a diverse field, encompassing research that spans dimensions from a tiny fraction of the volume of the individual particles (neutrons and protons) in the atomic nucleus to the enormous scales of astrophysical objects in the cosmos. Nuclear Physics: Exploring the Heart of Matter explains the research objectives, which include the desire not only to better understand the nature of matter interacting at the nuclear level, but also to describe the state of the universe that existed at the big bang. This report explains how the universe can now be studied in the most advanced colliding-beam accelerators, where strong forces are the dominant interactions, as well as the nature of neutrinos.

Final Report of the Committee on a Strategic Plan for U.S. Burning Plasma Research - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2019)
Fusion offers the prospect of virtually unlimited energy. The United States and many nations around the world have made enormous progress toward achieving fusion energy. With ITER scheduled to go online within a decade and demonstrate controlled fusion ten years later, now is the right time for the United States to develop plans to benefit from its investment in burning plasma research and take steps to develop fusion electricity for the nation's future energy needs. At the request of the Department of Energy, the National Academies of Sciences, Engineering, and Medicine organized a committee to develop a strategic plan for U.S. fusion research. The final report's two main recommendations are: (1) The United States should remain an ITER partner as the most cost-effective way to gain experience with a burning plasma at the scale of a power plant. (2) The United States should start a national program of accompanying research and technology leading to the construction of a compact pilot plant that produces electricity from fusion at the lowest possible capital cost.

Sustainability in the Chemical Industry: Grand Challenges and Research Needs - National Research Council (The National Academies Press, 2006)
Through innovative design, creation, processing, use, and disposal of substances, the chemical industry plays a major role in advancing applications to support sustainability in a way that will allow humanity to meet current environmental, economic, and societal needs without compromising the progress and success of future generations. Based on a workshop held in February 2005 that brought together a broad cross section of disciplines and organizations in the chemical industry, this report identifies a set of overarching Grand Challenges for Sustainability research in chemistry and chemical engineering to assist the chemical industry in defining a sustainability agenda. These Grand Challenges include life cycle analysis, renewable chemical feedstocks, and education, among others.

Manipulating Quantum Systems: An Assessment of Atomic, Molecular, and Optical Physics in the United States - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2020)
The field of atomic, molecular, and optical (AMO) science underpins many technologies and continues to progress at an exciting pace for both scientific discoveries and technological innovations. AMO physics studies the fundamental building blocks of functioning matter to help advance the understanding of the universe. It is a foundational discipline within the physical sciences, relating to atoms and their constituents, to molecules, and to light at the quantum level. AMO physics combines fundamental research with practical application, coupling fundamental scientific discovery to rapidly evolving technological advances, innovation and commercialization. Due to the wide-reaching intellectual, societal, and economical impact of AMO, it is important to review recent advances and future opportunities in AMO physics. Manipulating Quantum Systems: An Assessment of Atomic, Molecular, and Optical Physics in the United States assesses opportunities in AMO science and technology over the coming decade. Key topics in this report include tools made of light; emerging phenomena from few- to many-body systems; the foundations of quantum information science and technologies; quantum dynamics in the time and frequency domains; precision and the nature of the universe, and the broader impact of AMO science.

Twenty-Third Symposium on Naval Hydrodynamics - National Research Council
\

Twenty-Fourth Symposium on Naval Hydrodynamics - National Research Council (The National Academies Press, 2003)
This report is part of a series of reports that summarize this regular event. The report discusses research developments in ship design, construction, and operation in a forum that encouraged both formal and informal discussion of presented papers.

The Chemistry of Microbiomes: Proceedings of a Seminar Series - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2017)
The 21st century has witnessed a complete revolution in the understanding and description of bacteria in eco- systems and microbial assemblages, and how they are regulated by complex interactions among microbes, hosts, and environments. The human organism is no longer considered a monolithic assembly of tissues, but is instead a true ecosystem composed of human cells, bacteria, fungi, algae, and viruses. As such, humans are not unlike other complex ecosystems containing microbial assemblages observed in the marine and earth environments. They all share a basic functional principle: Chemical communication is the universal language that allows such groups to properly function together. These chemical networks regulate interactions like metabolic exchange, antibiosis and symbiosis, and communication. The National Academies of Sciences, Engineering, and Medicine2019s Chemical Sciences Roundtable organized a series of four seminars in the autumn of 2016 to explore the current advances, opportunities, and challenges toward unveiling this 201cchemical dark matter201d and its role in the regulation and function of different ecosystems. The first three focused on specific ecosystems2014earth, marine, and human2014and the last on all microbiome systems. This publication summarizes the presentations and discussions from the seminars.

Twenty-Second Symposium on Naval Hydrodynamics - National Research Council (The National Academies Press, 1999)
The Twenty-Second Symposium on Naval Hydrodynamics was held in Washington, D.C., from August 9-14, 1998. It coincided with the 100th anniversary of the David Taylor Model Basin. This international symposium was organized jointly by the Office of Naval Research (Mechanics and Energy Conversion S&T Division), the National Research Council (Naval Studies Board), and the Naval Surface Warfare Center, Carderock Division (David Taylor Model Basin). This biennial symposium promotes the technical exchange of naval research developments of common interest to all the countries of the world. The forum encourages both formal and informal discussion of the presented papers, and the occasion provides an opportunity for direct communication between international peers.

Twenty-First Symposium on Naval Hydrodynamics - National Research Council (The National Academies Press, 1997)

Atomic, Molecular, and Optical Science: An Investment in the Future - National Research Council (The National Academies Press, 1994)
This book responds to the call for a clear description of the role of basic science in meeting societal needs. It gives examples of societal benefits of atomic, molecular, and optical (AMO) science in a number of key areas, including industrial technology, information technology, energy, global change, defense, health and medical technology, space technology, and transportation. This volume highlights the role of lasers in trapping, cooling, and manipulating individual atoms and molecules to make possible ultraprecise atomic clocks, structural engineering at the atomic level (nanotechnology), and new approaches to the study of deoxyribonucleic acid (DNA). AMO science is shown to be a field that is both an intellectually important basic science and a powerful enabling science that supports many other areas of science and technology.